Chemical kinetics and reaction mechanisms - James H Espenson (New York McGraw Hill,Inc., 1995)
Reaction and reaction rates; Reaction with a simple kinetic form; Deduction of reaction mechanism; Reaction in solution; Reaction in extreme rates.
Keywords: Chemic dynamics, static and equilibrium